2008
DOI: 10.1002/joc.1834
|View full text |Cite
|
Sign up to set email alerts
|

Trends in extreme precipitation indices derived from a daily rainfall database for the South of Portugal

Abstract: ABSTRACT:The rainfall regime of the South of Portugal is Mediterranean with Atlantic influence. Long-term series of reliable precipitation records are essential for land and water resources management, climate-change monitoring, modelling of erosion and run-off, among other applications for ecosystem and hydrological impact modelling. This study provides a qualitative classification of 106 daily rainfall series from stations located in the South of Portugal and evaluates temporal patterns in extreme precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 43 publications
(81 reference statements)
3
80
1
5
Order By: Relevance
“…Klein-Tank and Konnen (2003) found that there has been a general increase in annual extreme precipitation across Europe over the period 1946-1999, while Haylock and Goodess (2004 showed that the trends of the number of days above the 1961-1990 90th percentile of wet-day amounts have different signs, due to the heterogeneous nature of the region. In southern Europe, mostly across the Mediterranean basin, it has been suggested that the heaviest rainfall events, or the contribution of heaviest events to the annual total, have increased in western areas (Brunetti et al, 2000(Brunetti et al, , 2001(Brunetti et al, , 2004Alpert et al, 2002;Gonzalez-Hidalgo et al, 2003;Costa and Soares, 2009), but this result is strongly dependent on the period examined Brugnara et al, 2012); on the contrary, in the eastern areas, no significant trend has been detected in the number of intense or extreme events (Zang et al, 2009;Kioutsioukis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Klein-Tank and Konnen (2003) found that there has been a general increase in annual extreme precipitation across Europe over the period 1946-1999, while Haylock and Goodess (2004 showed that the trends of the number of days above the 1961-1990 90th percentile of wet-day amounts have different signs, due to the heterogeneous nature of the region. In southern Europe, mostly across the Mediterranean basin, it has been suggested that the heaviest rainfall events, or the contribution of heaviest events to the annual total, have increased in western areas (Brunetti et al, 2000(Brunetti et al, , 2001(Brunetti et al, , 2004Alpert et al, 2002;Gonzalez-Hidalgo et al, 2003;Costa and Soares, 2009), but this result is strongly dependent on the period examined Brugnara et al, 2012); on the contrary, in the eastern areas, no significant trend has been detected in the number of intense or extreme events (Zang et al, 2009;Kioutsioukis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Costa and Soares (20009) [11] confirmed that using absolute approaches without metadata or complementary information makes it difficult to determine if changes in a station's time series result from inhomogeneities or simply from abrupt changes in the regional climate.…”
Section: Trend Change Analysismentioning
confidence: 97%
“…Different methods have been introduced to test the homogeneity of hydroclimatic variables [11,25,28]. In this study, two methods were applied.…”
Section: Homogeneity Testsmentioning
confidence: 99%
See 2 more Smart Citations